Ultra-low-power media access control protocol based on clock drift characteristics in wireless sensor networks. (July 2017) - Pak, Wooguil
Many researchers have analyzed sources of uncertainty in synchronization protocols for wireless sensor networks. However, very few researchers perform this work in depth, and failed to discover comprehensive characteristics since they worked with only one or two measurement intervals. To overcome this problem, extensive measurements were conducted and analyzed to find the characteristics of the sources according to various measurement intervals. Using the characteristics, a new media access control protocol, WideMAC, was designed to support a wide range of duty cycles for various applications. The transmission node in WideMAC calculates the wakeup time of the reception node before transmitting a packet and adaptively estimates the synchronization error size according to the synchronization interval from seconds to hours. To track the reception node's wakeup time for synchronization, WideMAC uses two estimation algorithms that estimate the wakeup time and the upper bound of the total timing error. Accurate estimation of the wakeup time results in a significant amount of energy saving at the transmission node. Finally, through extensive performance evaluations in a testbed, WideMAC confirmed that it can significantly outperform existing state-of-the-art protocols.